2002
DOI: 10.2337/diacare.25.6.1022
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Diabetes Screening on Quality of Life

Abstract: OBJECTIVE -Diagnosis of a chronic illness can have a negative impact on patients' perception of their well-being ("labeling" effect). We sought to determine the effects of a new diagnosis of diabetes, discovered by systematic screening, on patients' health-related quality of life (HRQoL) 1 year after diagnosis.RESEARCH DESIGN AND METHODS -We performed diabetes screening at the Durham Veterans Affairs Medical Center of 1,253 outpatients, aged 45-64 years, who did not report having diabetes. Our initial screen w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
63
2
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 31 publications
7
63
2
3
Order By: Relevance
“…This assumes that a negative screening test or a positive screening test followed by a negative diagnostic test does not have any clinically significant long-term consequences, although screening itself will potentially have an impact on both quality of life (by provoking anxiety or reassurance) and risk behaviour (due to individuals becomes more or less motivated to change their diet or lifestyle) depending on the context of screening (these issues are well described in papers by Speight 223 and Edelman and colleagues 224 ). It is assumed that these effects can be modified by providing appropriate information and support at the time of screening and have not been included in the modelling.…”
Section: Other Assumptionsmentioning
confidence: 99%
“…This assumes that a negative screening test or a positive screening test followed by a negative diagnostic test does not have any clinically significant long-term consequences, although screening itself will potentially have an impact on both quality of life (by provoking anxiety or reassurance) and risk behaviour (due to individuals becomes more or less motivated to change their diet or lifestyle) depending on the context of screening (these issues are well described in papers by Speight 223 and Edelman and colleagues 224 ). It is assumed that these effects can be modified by providing appropriate information and support at the time of screening and have not been included in the modelling.…”
Section: Other Assumptionsmentioning
confidence: 99%
“…Recently, studies in Europe and the USA have specifically explored the psychological effects of undergoing screening for Type 2 Diabetes and these tend to support the conclusions of Marteau's work. Some studies have assessed the impact of screening by asking patients to complete rating scales that measure their levels of anxiety, depression, and disease-specific worry (Eborall et al, 2007a;Park et al, 2008), or their health-related quality of life (Edelman et al, 2002b). Such studies have generally found no lasting or significant adverse psychological effects in terms of anxiety, depression, worry, or perceived quality of life after screening.…”
Section: The St Leonard's Practice Approach To Screening For Type 2 Dmentioning
confidence: 99%
“…Apesar disso, existe consenso: o DM impacta na QV (17). Estudos demonstram que pacientes com DM têm nível de QV menor do que os pacientes sem esta enfermidade (18). Neste possível impacto negativo da DM sobre a QV, os aspectos que estão envolvidos ainda não são claramente conhecidos (19).…”
Section: Diabetes Melito E Qualidade De Vidaunclassified